PENGARUH PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022) - Muflikhah, Imroatul; Luhgiatno, Luhgiatno (STIE PENA, 2023)
Company value is very important for go-public companies to achieve goals and targets in maximizing profits. Based on previous research, there are different results in terms of its influence on company value (research gap). This research aims to analyze the influence of profitability, liquidity and company size on company value. The independent variables used in this research are profitability, liquidity and company size. The dependent variable in this research is company value. In this study using secondary data derived from annual financial reports. The population in this study are manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange for the period 2019 - 2022. The sampling technique used was purposive sampling and the number of samples was 9 companies. The data analysis method uses the SPSS 25 program. The results of this study indicate that profitability has a positive and significant effect on firm value, while liquidity and firm size have no significant effect on firm value. The results of profitability, liquidity and company size simultaneously have a positive and significant effect on company value. Keywords: Profitability, Liquidity, Company Size, and Company Value.